THE EFFECTIVENESS OF FLEXIBLE WORKING ARRANGEMENTS AS A FORM OF DIGITAL TRANSFORMATION FROM THE PERSPECTIVE OF INDONESIAN GOVERNMENT EMPLOYEES - Emyana Sirait (Journal of Information Technology and Its Utilization, 2021)
During the COVID-19 pandemic, flexible working arrangements (FWA) in Indonesia become necessary. In the Indonesian government, the opportunities and technical concepts of FWA are still being formulated. The survey answered by 745 respondents or 18.6% of the total employees in the Ministry of Communications and Informatics (MCI) indicates employees' perception from various groups of ages, fields of work, and occupations. The results show that more than 80% thought FWA had positive impacts on individual performance and at the same time maintained organizational performance. Some remained challenges are related to the availability of internet access, household affairs, and coordination difficulties.